(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article provides a historical overview of the dialectic of governance and rhetoric in the social system since ancient times. The place, meaning and development of rhetoric in human society are analyzed, and the relationship between rhetoric and philosophy in culture is discussed. The place of orators in history, the social significance of praise and condemnation, and the artistic merits of orators who have left their mark on history are emphasized. A brief description of the meaning, forms and current state of the art of speech in the formation of the independent Kyrgyz state is given.